Extracellular matrix alterations in the skin of patients affected by psoriasis - Wagner, Mariana Fatima Muaccad Gama; Theodoro, Thérèse Rachell; Filho, Carlos D’. Apparecida Santos Machad; Oyafuso, Luiza Keiko Matsuka; Pinhal, Maria Aparecida Silva (BMC cell biology, 2021)
Psoriasis is a chronic inflammatory disease dependent upon a complex interaction between genetic predisposition and immunological factors. It is characterized by skin lesions throughout the body, causing great morbidity and affecting life quality. The present study aimed to evaluate the protein and mRNA expression of heparanase-1 (HPSE), heparanase-2 (HPSE2), syndecan-1 (SYND1), metalloproteinases (MMP2, MMP9), and tissue inhibitor metalloproteinases 2 (TIMP2) in skin samples. From each psoriasis patient, two samples were collected, one sample from a psoriasis plaque (n = 23) and the other sample from non-affected skin (n = 23), as well as tissue collected by blepharoplasty from control individuals (n = 18). Protein expression was investigated by immunohistochemistry, followed by digital quantification. Quantitative RT-PCR obtained mRNA expression. Statistical analyses were done, and p values < 0.05 were considered significant. A significant increase in protein and mRNA expression was observed in both heparanases (HPSE and HPSE2), and higher protein levels of MMP9 and TIMP2 were observed in the psoriasis plaque compared to the non-affected skin. The data point to a probable activation of MMP2 by TIMP2. Moreover, there was a significant increase in HPSE2, SYND1, MMP9, and TIMP2 in non-affected skin samples from patients with psoriasis than in the control sample (tissue obtained by individuals who do not have psoriasis). These results show a possible correlation between the characteristic inflammatory process and alterations in the expression of the extracellular matrix in psoriasis. The increased expression of HPSE2, SYND1, MMP9, and TIMP2, even in the absence of psoriatic plaque, indicates that these molecules may be involved with extracellular matrix changes in the initial alterations the psoriatic process and may be candidates for the development of target treatments.